Pacing and the Non-Invasive Evaluation of Myocardial Fatty Acid Metabolism by Means of 17-123I-Heptadecanoic Acid Scintigraphy - Duwel, C. M. B.; Visser, F. C.; van Eenige, M. J.; Roos, J. C.; Roos, J. P. (Nuklearmedizin - NuclearMedicine, 1988)
The extent of myocardial non-esterified fatty acid (NEFA) oxidation depends among other things on exogeneous NEFA supply and energy demand. In 6 patients with a multi-programmable pacemaker scintigraphy with 17-123Iodo-heptadecanoic acid (17-123I-HDA) was performed to investigate NEFA metabolism at two levels: at a control level (basal heart rate 69 ± 6) and at increased pace frequency (104 ± 5). In both situations the derived time-activity curves, measured during a period of 75 min, were fitted with a monoexponential plus a constant curve: A(t) = A(0).exp (-t ln2/T½) + C. The half-time value, the uptake measured as the peak activity and the relative size of the oxidation pool were determined. The median of the half-time value did not change: 24 min (range 19–31) in the control heart rate study and 22 min (19–27) during the increased pace frequency study. The median of the uptake increased significantly from 33 cpm/pixel/2 mCi/100 kg (23–34) to 40 cpm/ pixel/2 mCi/100 kg (35–42; p <0.05 Wilcoxon). The median of the relative size of the oxidation pool increased from 57% (52-62) to 69% (63–71; p <0.05). We conclude that during pacing the augmented need for NEFA resulted in a demonstrable increase in uptake and oxidation of 17-123I-HDA. This result suggests that radioiodinated NEFA may be a valuable tool to quantify non-invasively the level of the myocardial NEFA metabolism in the human heart.Die Oxidation freier Fettsäuren (FFA) im Herzmuskel ist neben anderen Faktoren von der Menge exogen angebotener FFA und dem kardialen Energiebedarf abhängig. Bei 6 Patienten mit programmierbarem Schrittmacher wurde eine 123J-Heptadekansäure-Szintigraphie durchgeführt, um den FFA-Stoffwechsel des Herzens unter Basalbedingungen (Herzfrequenz 69 ± 6) und bei schrittmacherinduzierter Tachykardie (Herzfrequenz 104 ± 5) durchgeführt. Bei beiden Untersuchungen wurden die erhaltenen kardialen Zeitaktivitätskurven mit einer monoexponentiellen Funktion und einer Konstante gefittet: A(t) = A(0) x Exp(-t x ln2/T½) + C. Es wurden die Halbwertszeit, der maximale Uptake und die relative Poolgröße der FFA-Oxidation ermittelt. Der Median der Halbwertszeit blieb unverändert: 24 min (Streubreite 19–31) unter Kontrollbedingungen und 22 min (19–27) während Frequenzstimulation. Der Median des Uptakes stieg signifikant von 33 cpm/Pixel/2 mCi/100 kg (23–34) auf 40 cpm/Pixel/2 mCi/ 100 kg (35–42; p <0,05; Wilcoxon-Test). Der Median der relativen Poolgröße des FFA-Oxidationspools nahm von 57% (52–62) auf 69% (63–71; p <0,05) zu. Wir folgern, daß während Frequenzstimulation der gesteigerte FFA-Bedarf zu einer nachweisbaren Zunahme von Uptake und Oxidation von 123J-Heptadekansäure führt. Diese Ergebnisse weisen darauf hin, daß radiojodmarkierte freie Fettsäuren zur Untersuchung des Grades der FFA-Oxidation im menschlichen Herzen nützlich sein könnten.